2018
DOI: 10.1093/pm/pny008
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophizing Interferes with Cognitive Modulation of Pain in Women with Fibromyalgia

Abstract: FM patients with higher levels of catastrophizing were less able to distract themselves from pain, indicative of catastrophizing-related impairments in pain modulation. These results suggest that the tendency to catastrophize interacts with attention-resource allocation and may represent a mechanism of chronic pain exacerbation and/or maintenance. Reducing catastrophizing may improve FM symptoms via improving central nervous system regulation of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 62 publications
3
47
2
1
Order By: Relevance
“…Chronic pain often coexists with anxiety, depression, and pain catastrophizing [38,70,71]. Their concurrent associations as well as the predictive value of pain catastrophizing on poor outcomes for patients with chronic pain have been demonstrated in previous studies [14,[19][20][21]23]. Changes in levels of pain catastrophizing by reducing emotional distress and maladaptive behaviours can result in better pain-related outcomes [72].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Chronic pain often coexists with anxiety, depression, and pain catastrophizing [38,70,71]. Their concurrent associations as well as the predictive value of pain catastrophizing on poor outcomes for patients with chronic pain have been demonstrated in previous studies [14,[19][20][21]23]. Changes in levels of pain catastrophizing by reducing emotional distress and maladaptive behaviours can result in better pain-related outcomes [72].…”
Section: Discussionmentioning
confidence: 92%
“…In this context, one's psychological state is an important determinant of pain experiences as well as mental health [10][11][12]. Brain images indicate that cognitive and emotional modulations of pain are associated with alterations in specific brain regions [13,14]. Clinically, psychological factors such as anxiety, catastrophizing, and depressive symptoms seem to be important features of patients with chronic pain [11,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCS correlate also with anxiety and depression [28]. In an elegant study that used functional magnetic resonance imaging, Ellingson and coworkers demonstrated that the tendency to catastrophism interferes with neural processes involved in pain modulation in FMS [29]. Acupuncture can, therefore, have powerful central effects in pain modulation, potentially also affecting cognitive aspects.…”
Section: Discussionmentioning
confidence: 99%
“…All types of pain are accompanied by changes in mood, attention, and motivation that exacerbate the sensory disturbance (60,61). The extent to which the sensory and affective components of pain are mechanistically linked remains to be fully determined.…”
Section: Dysfunctional Painmentioning
confidence: 99%